MEASUREMENT AND EVALUATION OF THE EARTH'S MAGNETIC FIELD BY MEANS OF THE SMALL SPACECRAFT ECUADOR-UTE (HC1PX) - Schitov, Aleksey; Dobroserdov, Oleg; Frolov, Sergey; Semenova , Ludmila (Journal of Applied Engineering Science, 2021)
The paper deals with the use of the small spacecraft ECUADOR-UTE (HC1PX) designed to conduct space experiments in autonomous flight conditions and, in particular, to measure the Earth’s electromagnetic field and study the ionosphere. The spacecraft has a built-in target load module, including a precision magnetometer that measures the Earth’s magnetic field. The measurement results are used to study the properties and state of the circumterranean environment including magnetic anomalies. The latter may indicate certain tectonic structures in the sedimentary stratum, which are indicators of oil and gas, and magnetic pole displacement processes. Measurement results can also be used for prediction and forecasting efforts in anomalouszones. The compiled analytical dependences for the anomalous zones can serve as a forecasting device when studying the magnetic tension of the Earth’s geographic regions by means of a spacecraft. Measuring the magnetic anomalies of the Earth’s surface is should prove necessary forfactoring them in and developingnational industries.
Keywords: approximation, prediction, forecast, space experiment.